(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction:Ocular trauma is a significant public health concern, often leading to vision impairment or blindness. In India, medico-legal considerations play a crucial role in the assessment and management of ocular injuries, necessi tating a comprehensive understanding of forensic evaluation, legal obligations, and clinical responsibilities.Objective: This review explores the medico-legal aspects of ocular trauma in India, analysing the epide miology, forensic assessment, legal implications, and challenges in clinical practice.Methods: A systematic review was conducted using electronic databases such as PubMed, Scopus, Google Scholar, and Indian Kanoon, focusing on studies published in the last 30 years. The review included peer-reviewed arti cles, legal statutes, forensic guidelines, and judicial precedents related to ocular trauma. Results and discussion: The incidence of ocular injuries remains high, particularly among males in occupational and road traffic accidents. Classification systems, such as the Ocular Trauma Score (OTS) and BETT classification, aid in prognosis and documen tation. Legal aspects include requirements for informed consent, medico-legal documentation, expert witness testimony, and liability in cases of medical negligence. The review highlights challenges in maintaining proper records, ethical considerations, and the need for increased medico-legal awareness among ophthalmologists.Conclusion:Medico-legal knowledge is essential for ophthalmologists to ensure legal compliance and ethical practice. Proper documentation, adherence to forensic guidelines, and understanding the implications of medical negligence can help safeguard both patients and practitioners.